Cherenkov oscillator operating at the second band gap of leakage waveguide structures - Kyu-Ha Jang; Seong Hee Park; Kitae Lee; Young Uk Jeong (AIP Advances, 2016)
An electromagnetic wave source operating around second band gaps of metallic grating structures is presented. The considered metallic grating structures are not perfect periodic but inhomogeneously structured within a period to have a second band gap where the wavelength is equal to the period of the structures. The radiation mechanism by an electron beam in the structures is different from the well-known Smith-Purcell radiation occurring in perfect periodic grating structures. That is, the radiating wave has a single frequency and the radiation is unidirectional. When the energy of the electron beam is synchronized at the standing wave point in the dispersion curves, strong interaction happens and coherent radiation perpendicular to the grating surface is generated with relatively lower starting oscillation current.